2012
DOI: 10.1021/ic3001619
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous CO2 Reduction by Ni(cyclam) at a Glassy Carbon Electrode

Abstract: The homogeneous CO(2) reduction activity of several nickel cyclam complexes was examined by cyclic voltammetry and controlled potential electrolysis. CO production with high efficiency from unsubstituted Ni(cyclam) was verified, while the activity was found to be attenuated with methyl substitution of the amines on the cyclam ring. Reactivity with CO(2) was also probed using density functional theory (DFT) calculations. The relative CO(2) binding energies to the Ni(I) state obtained from DFT were found to matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
343
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(364 citation statements)
references
References 31 publications
15
343
0
1
Order By: Relevance
“…2. In a N 2 -saturated condition, an irreversible reduction wave of Ni(II)/Ni(I) couple apprears at -1.22 V, which matches with prior studies reporting irreversible behaviors of Ni(II)/Ni(I) redox couple on a glassy carbon electrode in tri-HCl buffer and KCl solution [7,8]. Some other studies, however, reported quasi-reversible behaviors for the Ni(II)/ Ni(I) couple [5,6].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…2. In a N 2 -saturated condition, an irreversible reduction wave of Ni(II)/Ni(I) couple apprears at -1.22 V, which matches with prior studies reporting irreversible behaviors of Ni(II)/Ni(I) redox couple on a glassy carbon electrode in tri-HCl buffer and KCl solution [7,8]. Some other studies, however, reported quasi-reversible behaviors for the Ni(II)/ Ni(I) couple [5,6].…”
Section: Resultssupporting
confidence: 89%
“…In a CO 2 -saturated solution, a large reduction current corresponding to electrocatalytic CO 2 reduction is observed. The onset potential of the CO 2 reduction is determined to be -1.18 V, which is consistent with prior studies [5][6][7][8].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A further example of CO-selective CO 2 -reduction molecular electrocatalyst is Ni(cyclam) 2+ [77,78]. Interestingly, Ni(cyclam) 2+ has also been shown to be an effective mediator for the electrosynthesis of cyclic carbonates (50) from epoxides (49) and CO 2 Eq.…”
Section: Electrocarboxylation Reactionsmentioning
confidence: 99%